A new member of the genus Sinonatrix (Serpentes: Colubridae) from western China - Guo, Peng; Zhu, Fei; Liu, Qin (Zootaxa, 2019)
A new member of the natricine snake genus Sinonatrix Rossman & Eberle, 1977 is described from Yunnan Province, southwestern China, based on a single female specimen. The new species, Sinonatrix yapingi sp. nov., is distinguished from its congeners and related species by the following combination of characters: 1) large body size (maximum total length more than 795 mm); 2) dorsal scales in 19-19-17 rows, moderately keeled except outer four; 3) prefrontal single; 4) ventral scales 149, subcaudals 55, paired; 5) cloaca divided; 6) body bands 30; 7) belly milk-white, without speckles or bands; 8) reduction of dorsal scale rows from 19 to 17 anterior to 90th ventral scale; 9) reduction of caudodorsal scale rows from 8 to 6 anterior to 12th subcaudal and from 6 to 4 anterior to 38th subcaudal; 10) postorbital bones not in contact with frontals, with weak parietal ridge; end of supratemporal bones extending beyond braincase; maxillary teeth 25, last two not enlarged; and, dentary teeth 26. In addition, the genetic distances between the new species and other representatives of Sinonatrix ranged from 14.6% to 15.0%.